Standar Pelayanan Haji dan Umroh di PT Budi Luhur Abadi (Bilad Tour) Kantor Cabang Kota Bogor - Sobirin Sobirin; Uti Supriyatna; Afrig Afrig (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
In fact, there are still many problems that always arise, such as starting from the registration of the pilgrimage, the cost of the pilgrimage, accommodation and transportation for the pilgrimage, the management of the pilgrimage funds, to the failure of a number of prospective pilgrims to go to the holy land. This study uses a qualitative research method, with a literature and empirical approach, interview data collection techniques, observation and documentation. The results of the study show that: Standards for Hajj and Umrah Services at PT Budi Luhur Abadi (Bilad Tour), Bogo City Branch Offices include: Standards for Hajj and Umrah Bilad Tour services, Bogor City Branch Offices guided by the regulations of the Minister of Religion and the Law of the Republic of Indonesia, namely Number 17 of 1999 Article 14. In the implementation of services, all of them are guided by the standards of laws and regulations issued by the Ministry of Religion. Development of Hajj and Umrahdi Bilad Tour, Bogor City Branch Office. The last five years can be seen the development of the ups and downs in the acquisition of pilgrims for Hajj and Umrah that has occurred.Keywords: Hajj and Umrah Services; Bogor; PT. Nobility AbstrakPada kenyataannya masih banyak diketemukan problematika yang selalu muncul seperti mulai dari pendaftaran haji, biaya haji, akomodasi dan transportasi haji, pengelolaan dana haji, hingga gagalnya sejumlah calon jamaah haji plus berangkat ke tanah suci. Penelitian ini menggunakan metode penelitian Kualitatif, dengan pendekatan literatur dan empiris, teknik pengumpulan data wawancara, observasi dan dokumentasi. Hasil penelitian menunjukan bahwa:  Standar Pelayanan Haji dan Umrah di PT Budi Luhur Abadi (Bilad Tour), Kantor Cabang Kota Bogo meliputi: Standar pelayanan Haji dan Umrah Bilad Tour, Kantor Cabang Kota Bogor berpedoman pada peraturan peraturan Mentri Agama dan Undang undang Republik Indonesia yaitu Nomor 17 Tahun 1999 Pasal 14.  Dalam pelaksanaan pelayanan semuanya berpedoman pada standar undang-undang dan peraturan-peraturan yang di keluarkan oleh Kemenag. Perkembangan Haji dan Umrahdi Bilad Tour, Kantor Cabang Kota Bogor. Lima tahun terakhir ini bisa di lihat perkembangan naik turunya perolehan jamaah haji dan umrah yang telah terjadi.Kata Kunci: Pelayanan Haji dan Umroh; Bogor; PT. Budi Luhur